Immunotherapy-Associated Pancreatic Adverse Events: Current Understanding of Their Mechanism, Diagnosis, and Management - Liu, Ya; Zhang, Hao; Zhou, Li; Li, Weichun; Yang, Le; Li, Wen; Li, Kezhou; Liu, Xubao (Frontiers in Oncology, 2021)
Immune checkpoint inhibitors (ICIs) such as anti-programmed death-1 (PD-1) and its ligand PD-L1 and anti-cytotoxic T-lymphocyte antigen 4 (CTLA-4) monoclonal antibodies, are involved in T cell-mediated immune response augmentation and promote anti-tumor immunity. Cancer patients treated with combination of immunotherapy, chemotherapy, radiotherapy, and targeted therapy exhibit superior clinical outcomes and tolerance compared with patients treated with monotherapies. However, immutherapy is associated with several concomitant immune-related adverse events (irAEs). For instance, IrAEs interferes with function of gastrointestinal tract, endocrine, dermatological, nervous system and musculoskeletal systems. ICIs-associated pancreatic injury might causes decrease in endocrine and exocrine pancreatic function, resulting in metabolic and nutritional disorders. Clinicians who administer immune checkpoint inhibitors to cancer patients are diagnosed with hyperglycemia, abdominal pain and steatorrhea. Currently, the precise mechanism of ICIs-associated pancreatic injury has not been fully explored. This paper summarizes incidence, diagnosis, clinical characteristics, potential mechanisms, and treatment management patterns of ICIs-associated pancreatic AEs based on previous studies. In addition, possible management approaches of these adverse effects are presented in this paper. in the findings summarized in this paper lay a basis for management of ICIs-associated pancreatic AEs and expanding future immunotherapy applications.